KOMPETENSI PEDAGOGIS DIGITAL GURU PAI DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI KURIKULUM MERDEKA: ANALISIS KEBUTUHAN DAN TANTANGAN IMPLEMENTASI - Riyansyah; sabli, Muhammad; Kurniawan, Sugeng; Yulia Friska, Sonia; Baili; Andryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The implementation of the Merdeka Curriculum requires Islamic Religious Education (PAI) teachers to integrate differentiated learning with meaningful use of digital technology. However, the gap between policy and classroom practice indicates uneven digital pedagogical competence among PAI teachers in designing learning that responds to students' diverse learning profiles. This study aims to map needs and identify implementation challenges of PAI teachers' digital pedagogical competence in applying differentiated learning under the Merdeka Curriculum. The research employed a sequential explanatory mixed-methods design. The quantitative sample consisted of 156 junior and senior high school PAI teachers across three districts/cities selected via stratified random sampling. Quantitative data were collected using a digital pedagogical competence questionnaire (α=0.91) and professional development needs survey, analyzed descriptively and inferentially. The qualitative sample comprised 18 teachers selected purposively based on extreme competence scores, with in-depth interviews and FGDs. Thematic analysis revealed four main challenge dimensions: (1) infrastructure gaps and contextual digital literacy, (2) pedagogical unpreparedness in digitally diagnosing learning profiles, (3) administrative burden and assessment misalignment, and (4) ethical-spiritual dilemmas in integrating technology into religious education. Findings show that 68% of PAI teachers are at a basic digital competence level, with the highest training needs in data-driven differentiation design and adaptive formative assessment. This study recommends a sustained digital-based Professional Learning Community (PLC) mentoring model, administrative policy simplification, and development of digital pedagogical modules integrated with Islamic values. The results contribute to strengthening PAI teacher competence development policies in the Merdeka Curriculum era.